Extreme virtue : truth and leadership in five great American lives - Sartwell, Crispin, 1958- (State University of New York Press, 2003)
"Extreme Virtue presents a new and radical approach to the problems of leadership and virtue in public life. Originating in the author's newspaper writing about the Clinton/Lewinsky scandal, the book grapples with what has gone wrong in the American political system and describes what we should look for in our leaders and that more can be accomplished by straight talk than by polling and focus groups."--Jacket
Keywords: Virtues -- Case studies.; Conduct of life -- Case studies.; Leadership -- Moral and ethical aspects -- United States -- Case studies.; Conduct of life.; Vertus -- Études de cas.; Morale pratique -- Études de cas.; Leadership -- Aspect moral -- États-Unis -- Études de cas.; Morale pratique.; ethics (philosophical concept); SELF-HELP -- Personal Growth -- Happiness.; Conduct of life; Leadership -- Moral and ethical aspects; Virtues; United States; Case studies